Strengthening the Online Marketing Capacity of Agensia Hayati Through Facebook: A Strategy for the Menur Women Farmers Group - Latif Nur Huda; Endah Puspitojati; Nicky Oktav Fauziah (PAKIS JOURNAL INSTITUTE, 2026)
Menur Women Farmers Group (Kelompok Wanita Tani, KWT) is a farmer institution engaged in the production and provision of biological control agents in Murtigading Village, Sanden Kapanewon, Bantul Regency. Although the group has adequate production capacity and good technical skills, the marketing of KWT Menur products still faces several constraints, particularly limited digital promotion and weak product brand identity. This study aimed to analyze internal and external factors, formulate an online marketing strategy through Facebook, and develop a community empowerment design to strengthen the marketing capacity of KWT Menur. This study employed a mixed-methods approach with an embedded design. Data were collected from 25 respondents through observation, in-depth interviews, documentation, questionnaires, and Focus Group Discussion (FGD). Data were analyzed using the IFAS, EFAS, SWOT, and Quantitative Strategic Planning Matrix (QSPM) matrices. The results showed that the group’s internal condition was strong, with an IFAS score of 2.902, while the external environment was supportive, with an EFAS score of 2.976. These results placed KWT Menur in Quadrant I, indicating an aggressive growth strategy. The QSPM analysis showed that the main priority strategy was strengthening the branding of environmentally friendly products, with a Total Attractiveness Score (TAS) of 7.516. Strengthening branding, improving product packaging, and enhancing digital marketing skills through Facebook are expected to expand market reach, increase product competitiveness, and support the sustainability of the biological control agent enterprise managed by KWT Menur.